2016
DOI: 10.1039/c5sc01565k
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(ii)-polypyridyl zirconium(iv) metal–organic frameworks as a new class of sensitized solar cells

Abstract: Ruthenium(ii) polypyridyl-doped metal–organic framework sensitized films on TiO2 for photovoltaics reveal that the preparative method of dye doping/incorporation into the MOF is integral to the total solar cell efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 73 publications
(72 reference statements)
2
105
1
Order By: Relevance
“…Metal organic frameworks are a class of materials that have been successfully proposed for applications in quite different fields, from catalysis to gas separation 1,2 and photovoltaics. [3][4][5] At the basis of the interest in these materials, there is the possibility of tailoring their structure to target applications by appropriately changing their structural building blocks (organic ligands and metal nodes). With respect to applications, a strong obstacle is represented by their well-earned reputation as air and moisture sensitive materials.…”
mentioning
confidence: 99%
“…Metal organic frameworks are a class of materials that have been successfully proposed for applications in quite different fields, from catalysis to gas separation 1,2 and photovoltaics. [3][4][5] At the basis of the interest in these materials, there is the possibility of tailoring their structure to target applications by appropriately changing their structural building blocks (organic ligands and metal nodes). With respect to applications, a strong obstacle is represented by their well-earned reputation as air and moisture sensitive materials.…”
mentioning
confidence: 99%
“…Although the excited state behavior of a handful of MOFs has been measured in the context of DSSCs [31,32] , nobody has investigated their sub-nanosecond behavior. Since this is the typical timescale for electron injection from traditional molecular sensitizers, this seems to be a valuable area of study.…”
Section: Ultrafast Laser Spectroscopy Measurementsmentioning
confidence: 99%
“…At different doping concentrations, the doping RuDCBPY experienced different solvation environments leading to the nonexponential behavior showed at higher doping concentrations. It was also reported that RuDCBPY‐doped UiO‐67 could be grown onto the glass substrates coated with the conductive fluorine‐doped tin oxide (FTO) without changing the excited state properties of the material . Before long, RuDCBPY‐doped UiO‐67 films were studied to grow onto TiO 2 and in order to generate a sensitizing material for photovoltaic solar cell applications in the report of Maza et al .…”
Section: Uio‐67 Derivativesmentioning
confidence: 99%